Enhancing EFL instruction: The impact of digital visual aids on pre-service teacher training - Paul Gonzalez-Torres; Eliana Pinza-Tapia (Studies in English Language and Education, 2026)
The purpose of the study was to explore how digital visual aids enhanced English as a Foreign Language (EFL) pre-service teachers’ comprehension, engagement, and teaching effectiveness, as well as their perceptions of these aids. The research employed a mixed-method approach, combining a quasi-experimental design with a survey research design and qualitative data. The participants were 68 EFL pre-service teachers enrolled in a Teaching English as a Foreign Language (TEFL) program, divided into an experimental group, who learned through digital visual aids, and a control group, who received traditional instruction. The two groups received four hours of instruction per week for four months. The instruments included pre- and post-tests to measure the level of knowledge acquired, a questionnaire to measure perceptions toward visual aids, and a focus group discussion to obtain qualitative data. The results indicated that the experimental group achieved greater improvements in comprehension and instructional effectiveness than the control group. In contrast, the control group showed only modest gains between the pre- and post-tests. Additionally, the participants had positive perceptions about the use of digital visual aids in their academic training. The main benefits mentioned included the improvement of content retention, simplification of complex ideas, and the ability to connect new concepts to previous knowledge. However, challenges identified involved excessive dependence on the use of visuals and the time invested in designing digital visual aids.